Case Report: MAP2K1 K57N mutation is associated with primary resistance to anti-EGFR monoclonal antibodies in metastatic colorectal cancer - Mauri, Gianluca; Patelli, Giorgio; Gori, Viviana; Lauricella, Calogero; Mussolin, Benedetta; Amatu, Alessio; Bencardino, Katia; Tosi, Federica; Bonazzina, Erica; Bonoldi, Emanuela; Bardelli, Alberto; Siena, Salvatore; et al. (Frontiers in Oncology, 2022)
Background: We aim to identify the prevalence and the role of the MAP2K1 K57N mutation in predicting resistance to anti-EGFR agents in metastatic colorectal cancer (mCRC) patients. Methods: We retrospectively reviewed tumor-based next generation sequencing (NGS) results from mCRC patients screened for enrollment in the STARTRK-2 clinical trial between July 2019 and March 2021. Then, in patients harboring MSS RAS and BRAF wild-type MAP2K1 mutant mCRC, we reviewed outcome to treatment with anti-EGFR monoclonal antibodies. Results: A total of 246 mCRC patients were screened. Most of them, 215/220 (97.7%), were diagnosed with MSS mCRC and 112/215 (52.1%) with MSS, RAS and BRAF wild-type mCRC. Among the latter, 2/112 (1.8%) had MAP2K1 K57N mutant mCRC and both received anti-EGFR monotherapy as third line treatment. In both patients, MAP2K1 K57N mutant tumors proved primary resistant to anti-EGFR agent panitumumab monotherapy. Of interest, one of these patients was treated with anti-EGFR agents three times throughout his course of treatment, achieving some clinical benefit only when associated with other cytotoxic agents (FOLFOX or irinotecan). Conclusion: We verified in a clinical real-world setting that MAP2K1 K57N mutation is a resistance mechanism to anti-EGFR agents in mCRC. Thus, we suggest avoiding the administration of these drugs to MSS RAS and BRAF wild-type MAP2K1 N57K mutant mCRC.